Donepezil improves learning and memory deficits in APP/PS1 mice by inhibition of microglial activation. (2nd April 2015) - Guo, H.B.; Cheng, Y.F.; Wu, J.G.; Wang, C.M.; Wang, H.T.; Zhang, C.; Qiu, Z.K.; Xu, J.P.
Highlights: Donepezil inhibited mircoglial activation in APP/PS1 mice. Donepezil reduced the level of proinflammatory cytokines in APP/PS1 mice. Donepezil increased the expression of IDE, which is a degrading enzyme of Aβ. Donepezil decreased insoluble Aβ40/Aβ42 and soluble Aβ40 levels in APP/PS1 mice. The neuroprotection of donepezil may be due to its anti-inflammatory effects. Abstract: Donepezil, a cholinesterase inhibitor, is a representative symptomatic therapy for Alzheimer's disease (AD). Recent studies have reported the anti-inflammatory effects of donepezil. However, limited studies that investigate its anti-inflammatory effect in AD have been reported. Considering the role of proinflammatory molecules and microglial activation in the pathogenesis of AD, the current study aimed to elucidate the effects of donepezil on microglial activation induced by amyloid deposition in transgenic mice. Our results showed that chronic treatment with donepezil significantly improved the cognitive function in the novel object recognition test and Morris water maze test in amyloid precursor protein (APP)/presenilin-1 (PS1) transgenic mice. We further demonstrated that these cognitive enhancements were related to the anti-inflammatory effect of donepezil. We found that donepezil could inhibit the expression of CD68, a specific marker of microglial activation, and reduce the release of proinflammatory cytokines including tumor necrosis factor-α and interleukin-1β. Immunohistochemistry and Congo red co-staining revealed that congophilic amyloid and activated microglia around plaques were also reduced by donepezil treatment. Enzyme-linked immunosorbent assay (ELISA) analysis showed that donepezil decreased insoluble Aβ40/Aβ42 and soluble Aβ40 levels. Moreover, donepezil reversed the impaired expression of insulin-degrading enzyme in the hippocampus of APP/PS1 mice. Our findings indicated that donepezil improves cognitive deficits in APP/PS1 mice by a mechanism that may be associated with its inhibition of microglial activation and release of proinflammatory cytokines.